2018
DOI: 10.1002/stem.2923
|View full text |Cite
|
Sign up to set email alerts
|

Human Cartilage-Derived Progenitors Resist Terminal Differentiation and Require CXCR4 Activation to Successfully Bridge Meniscus Tissue Tears

Abstract: Meniscus injuries are among the most common orthopaedic injuries. Tears in the inner one-third of the meniscus heal poorly and present a significant clinical challenge. In this study, we hypothesized that progenitor cells from healthy human articular cartilage (C-PCs) may be more suitable than bone-marrow mesenchymal stem cells (BM-MSCs) to mediate bridging and reintegration of fibrocartilage tissue tears in meniscus. C-PCs were isolated from healthy human articular cartilage based on their expression of mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 36 publications
4
50
0
Order By: Relevance
“…A recent study has confirmed that chondro-progenitors are more suitable candidates for therapeutic treatment of meniscus injury than BM-MSCs since they resisted to hypertrophic differentiation during tissue repair [86]. Similarly, and according with our findings, we can suggest that PL-induced activation of such CPC population able to counteract cell hypertrophy within articular cartilage could be considered beneficial in therapeutic treatments for OA.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study has confirmed that chondro-progenitors are more suitable candidates for therapeutic treatment of meniscus injury than BM-MSCs since they resisted to hypertrophic differentiation during tissue repair [86]. Similarly, and according with our findings, we can suggest that PL-induced activation of such CPC population able to counteract cell hypertrophy within articular cartilage could be considered beneficial in therapeutic treatments for OA.…”
Section: Discussionsupporting
confidence: 89%
“…It has been previously surmised that the C-PC is an ideal cell type for cartilaginous tissue repair/regeneration based on: (1) their natural placement within articular cartilage tissue [ 17 ], (2) their functional phenotype (i.e., chondrogenic capacity, resistance to terminal differentiation) [ 16 , 18 ]. It is demonstrated that C-PCs exhibit low basal expression of cell hypertrophy markers during in vitro cell culture [ 16 ] and ex vivo tissue coculture, in comparison to BM-MSCs [ 18 ]. Despite differences in their functional phenotype, C-PCs and BM-MSCs share similar immunophenotypic cell surface marker profiles ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite differences in their functional phenotype, C-PCs and BM-MSCs share similar immunophenotypic cell surface marker profiles ( Figure 1 ). Veritably, C-PCs satisfy the criteria outlined by the International Society for Cellular Therapy for characterizing mesenchymal stromal/stem cells [ 18 , 19 ]. Like BM-MSCs, C-PCs do not exhibit common hematopoietic stem cell surface markers CD34 and CD45; nor do they exhibit mononuclear peripheral blood-derived cell surface markers CD14 and CD11b ( Figure 1 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…In culture of man-made injured meniscus explants in vitro, meniscus-derived pluripotent cells could bridge and reintegrate torn meniscal fibrocartilage along the tear channel, as evidenced by the migratory ability in response to the chemokine signaling stromal-derived factor-1/stromal-derived factor-1 receptor (SDF-1/ CXCR4) axis, a pronounced tendency toward chondrogenic differentiation, a greater than 100% increase in fibrochondrocyte proliferation, the elevated expression of Sox9 and decreased expression of type X collagen, and the resistance to cellular hypertrophy and terminal differentiation during the tissue repair process in a rat [47] and a rabbit [19] model. On this basis, Jayasuriya et al [47] proposed that the initiation of the observed meniscal tissue repair is possible without first forming a blood clot, provided that an influx of stem cells is readily available near the damage site. Furthermore, the intraarticular injection of meniscus-derived pluripotent cells can enhance the regeneration of the injured meniscus at an early stage of OA, promoting neotissue formation with an improved shape and increased mature ECM and resulting in reduced expression of OA markers such as type I collagen, type X collagen, and hypoxia-inducible factor 2a (HIF-2a) but increased expression of collagen II [17,18].…”
Section: Migratory Abilitymentioning
confidence: 99%